A coupled level set and volume-of-fluid simulation for heat transfer of the double droplet impact on a spherical liquid film. (3rd April 2017) - Hong, Wenpeng; Wang, Yibo
ABSTRACT: A coupled level set and volume-of-fluid method is applied to investigate the double droplet impact on a spherical liquid film. The method focuses on the analysis of surface curvature, droplet diameter, impact velocity, double droplets vertical spacing, the thickness of the liquid film of two liquid droplets after the impact on a spherical liquid film, and the influence of flow and heat transfer characteristics. The results indicate that the average wall heat flux density of the double liquid droplet impact on a spherical liquid film is greater than that of a flat liquid film. Average wall heat transfer coefficient increases with the increase in the liquid film's spherical curvature. When the liquid film thickness is smaller, the average wall heat flux density of the liquid film is significantly reduced by the secondary droplets generated from the liquid film. When the liquid film thickness is larger, the influence of liquid film thickness on the average wall heat flux density gradually decreases. The average wall heat flux density increases with the increase in impact velocity and the droplet diameter; it also decreases with the increase in double droplets vertical spacing.